The paradigm of patient must evolve: Why a false sense of limited capacity can subvert all attempts at patient involvement - Dave deBronkart (The Beryl Institute, 2017)
This essay reviews the role of paradigms in molding the thoughts of a scientific field and looks rigorously at what two key terms mean – empowered and engaged – and how their interaction points to a new way forward, requiring a re-examination of our “paradigm of patient.” Five years ago, the Institute of Medicine’s Best Care at Lower Cost declared that patient-clinician partnerships are a cornerstone of a learning health system, a declaration that’s foundational to the era of involvement. How can we engineer that era correctly if our conception of “patient” is out of date? And how can we validate whether our model works? In the past eight years, the author has spoken at or participated in over 500 events in sixteen countries, and although declaring himself “just a patient,” he has observed persistent cultural patterns that make one thing clear: there is a need to change our understanding of the role of the patient in achieving best possible care.